KAJIAN PENERIMAAN DAN PENGGUNAAN SISTEM E-COMMERCE BERDASARKAN KERAGAMAN USIA, JENIS KELAMIN, PENGALAMAN PENGGUNANYA : STUDI KASUS BUKALAPAK.COM - Robi Sopandi (LPPM Universitas Bina Sarana Informatika, 2012)
The result of a research information system that aims to determine the factors that influence acceptance and use of e-commerce systems (bukalapak.com) and focus on testing based on the diversity between the sexes, age and the online transaction experience of factors that support the behavioral acceptance and use of e-commerce systems. This study is an empirical study using purposive sampling techniques in data collection. The data used are primary data using aquestionnaire. Individual research subjects are users of e-commerce system, especially students and lecturers BSI karwang. Some 192 participants participated as respondents in this study. The technology adoption model used is model UTAUT (Unified Theory of Acceptance and Use of Technology) which is the unification of the models of previous technology adoption. In addition totesting the theory, the study was also conducted to test the variables in the model UTAUT that affect the acceptance and use of e-commerce systems (bukalapak.com). Data analysis was performed with the approach to Structural Equation Modeling (SEM) is a covariance-based SEM with AMOS program 18. From the results obtained by SEM analysis that the model does not fit.Therefore, modification model to test the hypothesis. The results of this study demonstrate that effort expectancy and facilitating factors condition (the existence of facilities that support a system) influence the acceptance and use (bukalapak.com) then there is a difference variables moderating towards the acceptance and use of e-commerce systems (bukalapak.com).Keywords: E-Commerce, Unified Theory of Acceptance and Use of Technology (UTAUT),Structural Equation Modeling (SEM), AMOS